2018
DOI: 10.1021/acsmedchemlett.8b00381
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Artemisinin–Estrogen Hybrids Highly Active against HCMV, P. falciparum, and Cervical and Breast Cancer

Abstract: Artemisinin−estrogen hybrids were for the first time both synthesized and investigated for their in vitro biological activity against malaria parasites (Plasmodium falciparum 3D7), human cytomegalovirus (HCMV), and a panel of human malignant cells of gynecological origin containing breast (MCF7, MDA-MB-231, MDA-MB-361, T47D) and cervical tumor cell lines (HeLa, SiHa, C33A). In terms of antimalarial efficacy, hybrid 8 (EC 50 = 3.8 nM) was about two times more active than its parent compound artesunic acid (7) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…In recent years, many C10‐derivatized DHA hybrids have been reported in the literature. For example, DHA conjugated with naturally occurring active molecules such as coumarin, cinnamic acid, chalcones, N ‐aryl phenylethenesulfonamides, thymoquinone and estradiol, all with anticancer activity themselves, have been tested against a variety of cancer cell lines. Our research has been mainly focused on the study of biologically active hybrids based on bile acids (BAs); therefore, we considered BAs as suitable partners for the preparation of novel DHA hybrids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many C10‐derivatized DHA hybrids have been reported in the literature. For example, DHA conjugated with naturally occurring active molecules such as coumarin, cinnamic acid, chalcones, N ‐aryl phenylethenesulfonamides, thymoquinone and estradiol, all with anticancer activity themselves, have been tested against a variety of cancer cell lines. Our research has been mainly focused on the study of biologically active hybrids based on bile acids (BAs); therefore, we considered BAs as suitable partners for the preparation of novel DHA hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…properties can improve the cytotoxicity and cytoselectivity toward target cancerc ells or other properties, such as bioavailability.T his latter approachm ight represent an interesting strategyf or the development of new anticancer drugs. In recent years, many C10-derivatized DHA hybridsh ave been reported in the literature.F or example, DHA conjugated with naturallyo ccurring active molecules such as coumarin, [10] cinnamic acid, [11] chalcones, [12] N-aryl phenylethenesulfonamides, [13] thymoquinone [14] and estradiol, [15] all with anticancer activity themselves, have been tested against av arietyo f cancer cell lines. Our research has been mainly focusedo nt he study of biologically active hybrids based on bile acids (BAs); [16] therefore, we considered BAs as suitable partners for the preparation of novel DHA hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Tsogoeva et al (2018) 54 reported the synthesis of artemisinin-estrogen hybrids and their antimalarial activity against the CQ S 3D7 strain of P. falciparum. These hybrids exhibited excellent to moderate antimalarial efficacy, with EC 50 values ranging from 3.8 to 128.8 nM, while their estrogen precursors showed no activity (EC 50 > 16 000 nM).…”
Section: Artemisinin-estrogen Hybridsmentioning
confidence: 99%
“…It was concluded that a methoxy group instead of a benzyloxy subunit at C-3 of the estrogen moiety seems to be more beneficial for antimalarial activity of artemisinin-estrogen hybrids. 54 55 reported first artemisinin-ferrocene hybrids comprising 1,2-disubstituted ferrocene analogs added by a piperazine linker to an artemisinin core at the C-10 position. Ferrocene (in the Fe 2+ state) undergoes facile oxidation to ferrocenium (Fe 3+ ), and is finally reduced by NADH and glutathione (GSH) to produce ferrocene.…”
Section: Artemisinin-estrogen Hybridsmentioning
confidence: 99%
“…The combination of artemisinin-type drugs with anticancer drugs can enhance the activity of the anticancer drugs in vitro or in vivo. 9,10,17,18 Given the therapeutic properties of tetronamides and the lack of artemisone-piperazine-tetronamide hybrids reported in the literature, we designed and synthesised a series of hybrid tetronamide derivatives possessing an artemisone-piperazine moiety (12a-f, Scheme 4) to evaluate their in vitro cytotoxicity and compare with VCR and ARA. Then we also research the effects of iron ions (Fe 2+ ) on cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%